CeO2‐CrOy/γ‐Al2O3 redox catalyst for the oxidative dehydrogenation of propane to propylene. (13th July 2020) - Zuo, Cheng; Wu, Man; Zhang, Xiuli; Guo, Qingjie
Abstract: CeO2 ‐CrOy loaded on γ‐Al2 O3 was investigated in this work for the oxidative dehydrogenation (ODH) of propane under oxygen‐free conditions. The ODH experiments of propane were conducted in a fluidized bed at 500°C‐600°C under 0.1 Mpa. The prepared catalyst was characterized by N2 adsorption‐desorption measurements, H2 ‐temperature‐programmed reduction, O2 ‐temperature‐programmed desorption, NH3 ‐temperature‐programmed desorption, x‐ray photoelectron spectroscopy, and x‐ray diffraction. The change in the selectivity of propylene resulted from the thermal cracking of the propane and the competition for lattice oxygen in the catalyst between propylene formation and propane and propylene combustion. Therefore, to achieve higher propylene yield in the industry, the reaction temperature should be 550°C‐575°C for the 17.5Cr‐2Ce/Al catalyst. The results of H2 ‐TPR (from 0.2218 mmol/g‐0.3208 mmol/g) revealed that the addition of CeO2 can enhance the oxygen capacity of CrOy . Compared with that for 17.5Cr/Al, the conversion can be enhanced from 22.4% to 28.5% and the selectivity of propylene can be improved from 72.2% to 75.9% for the 17.5Cr‐2Ce/Al catalyst. In addition, CeO2 can inhibit the evolution of lattice oxygen (O 2− ) to electrophilic oxygen species (O2 − ), causing the average COx (CO and CO2 ) selectivity to decrease from 9.64% to 6.31%.